DIAGNOSTIC AND TACTICAL ERRORS IN THE MANAGEMENT OF PATIENTS WITH PHEOCROMOCYTOMA - A.D. GAIBOV; O. NEMATZODA; F.S. SHOEV; Z.V. GOIBOVA (Avicenna Tajik State Medical University, 2023)
Objective: To analyze the causes of diagnostic and tactical errors in the management of patients with pheochromocytoma (PCC) and to develop a respective treatment and diagnostic algorithm. Methods: The mistakes made during clinical and instrumental diagnostics, preoperative preparation, and treatment of 55 patients with PCC were analyzed. Among the patients, there were 38 women (69.1%), and 17 men (30.9%). The mean age of the patients was 35.9±6.2 years. In 23 (41.8%) patients, right-sided localization of the tumor was noted, in 29 (52.7%) - left-sided one, while bilateral adrenal lesion occurred in 3 (5.5%) patients. The duration of arterial hypertension (AH) ranged from 6 months to 10 years (mean 4.56±1.7 years). Results: In 52.7% of cases, patients visited a doctor after more than three years from the onset of the first symptoms of the disease. The reasons for late treatment were: an insufficient examination of patients for the symptomatic genesis of hypertension due to low awareness of primary care physicians, self-administration of antihypertensive drugs, and treatment of patients by traditional healers. Errors in the interpretation of the results of ultrasound examination and computed tomography (CT) were noted in 7.3% of cases. During preoperative preparation, tactical errors were made in 7 patients, when instead of α-blockers, antihypertensive drugs of another class were prescribed, as a result of which two of the patients developed the syndrome of "uncontrolled hemodynamics" and died. In 5.5% of cases with large size of the tumor, iatrogenic injury to the inferior vena cava (IVC) and vessels of the right kidney occurred during the operation. In a histological examination of removed pheochromocytomas, the misinterpretation rate was 3.6%, and the diagnosis was reconsidered during repeated assessment. Conclusion: In more than half of the cases, during the primary diagnosis and treatment of PCC, various errors were made due to non-targeted examination of patients, incorrect interpretation of the results of radiological methods of examination, inadequate preoperative preparation of patients, as well as the iatrogenic injuries. In order to timely identify the discussed pathology in patients with AH, it is necessary to examine them in a targeted way for PCC. The basic medications for preoperative preparation of patients should be selective α-adrenoblockers. In order to prevent iatrogenic injuries of large vessels and organs of the retroperitoneal space, a thorough preoperative study of their relations with the tumor is necessary, as well as an improvement of the practical skills of the operating doctors.